2017
DOI: 10.1016/j.ajpath.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Promotes Cholangiocarcinoma Growth in Xenograft Mice

Abstract: Nicotine, the main addictive substance in tobacco, is known to play a role in the development and/or progression of a number of malignant tumors. However, nicotine's involvement in the pathogenesis of cholangiocarcinoma is controversial. Therefore, we studied the effects of nicotine on the growth of cholangiocarcinoma cells in vitro and the progression of cholangiocarcinoma in a mouse xenograft model. The predominant subunit responsible for nicotine-mediated proliferation in normal and cancer cells, the α7 nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Similarly, the unbiased PCA also demonstrated distinct signatures that could separate these two groups ( Figure 4 D). KEGG functional enrichment analysis showed that up-regulated DhMGs in the lung cancer group are mainly enriched in nicotine addition, calcium signaling pathway, and circadian entrainment pathways, which are closely associated with cancer development [32] , [33] ( Figure 4 E). Genes with decreased 5hmC signal were enriched in several cancer- and metastasis-related pathways including platelet activation pathway, cGMP-PKG signaling pathway, Rap signaling pathway, and PI3K-Akt signaling pathway [34] , [35] ( Figure 4 F).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the unbiased PCA also demonstrated distinct signatures that could separate these two groups ( Figure 4 D). KEGG functional enrichment analysis showed that up-regulated DhMGs in the lung cancer group are mainly enriched in nicotine addition, calcium signaling pathway, and circadian entrainment pathways, which are closely associated with cancer development [32] , [33] ( Figure 4 E). Genes with decreased 5hmC signal were enriched in several cancer- and metastasis-related pathways including platelet activation pathway, cGMP-PKG signaling pathway, Rap signaling pathway, and PI3K-Akt signaling pathway [34] , [35] ( Figure 4 F).…”
Section: Resultsmentioning
confidence: 99%
“…Also, higher densities of muscarinic Ach receptor 3 (M3) showed an association with high-grade differentiation of PDAC, more lymph node metastasis and a shorter patient overall survival (OS) [44]. In CCA, the presence of the cholinergic system plays a role in CCA cell proliferation and growth [46,47].…”
Section: Acetylcholine (Ach)mentioning
confidence: 99%
“…Similarly, it has been reported that α7nAChR is one of the predominantly expressed nicotinic receptors in both LC cell lines and primary hepatoma cells, demonstrating that these receptors may play crucial roles in the regulation of LC development and progression [9]. This receptor is more highly expressed in LC cells compared with normal cells and serves as a predominant protein responsible for nicotine-mediated LC progression [78]. Previous studies have shown the involvement of α7nAChR in liver pathological processes such as promoting carcinogenesis pathways in the liver.…”
Section: α7nachr and Liver Cancermentioning
confidence: 76%
“…Aizawa et al have shown that NNK as a high-affinity ligand of the α7nAChR through increased expression and activation of this receptor caused to hepatic damage and HCC progression in an animal model [79]. Similarly, Martínez and colleagues study suggest that nicotine acts through α7nAChR to stimulate the cholangiocyte proliferation in both in vitro and in xenograft mice model of LC [78]. In this context, the anti-tumor activity of acetylcholinesterase in HCC cells can also be justified by considering the fact that ACh is an important endogenous activator of α7nAChR [80].…”
Section: α7nachr and Liver Cancermentioning
confidence: 94%